Ta’wīl Teologis Abū Mansūr Al-Māturīdī (Pembacaan Kritis atas Ayat-ayat Keesaan Tuhan) - Tazkiyah, Izzatu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Historically, the discourse of exegesis and ta’wīl does not always go hand in hand. This was the case, especially when the al-Asy’ārī school of thought was in power. In this era, the exegesis had been positioned superior to the ta’wīl whose existence was not only regarded as the Islamic opposition but also the deviation of the truth. In this study, the author attempts to unveil the theological ta’wīl of al-Māturīdī on his magnum opus Ta’wīlat Ahl al- Sunnah and Kitab al-Tawhid. By considering its capability of reconciling traditionalists (Ash'ariyah) with rationalists (Muktazilah), the magnum opus of al-Maturidi’s becomes a research object of the current study. In particular, this study investigates the research object by means of comparative theological and exegesis approaches, with three main findings. The first finding shows that the concept of ta’wīl constructed by al-Māturīdī in his general exegesis seems very loose. The second finding demonstrates that the objectivity of the meaning presented by al-Māturīdī sometimes reduces due to its theological views which appear subjective. The third finding reveals a contradiction. On one side, al-Maturidi’s theological view can assuage any ideas that clash with Islam. On another side, however, al- Māturīdī tried to base the doctrine of Sunni theology.